From kesterite 2D nanosheets to wurtzite 1D nanorods: controllable synthesis of Cu−Zn−Sn−S and their application in electrocatalytic hydrogen evolution - Li, Yu; Wang, Shuaibing; Chen, Jie; Lin, Ouyang; Yin, Zhe; Yang, Chunhe; Tang, Aiwei (Journal of semiconductors, 2023)
As typical quarternary copper-based chalcogenides, Cu–Zn–Sn–S nanocrystals (CZTS NCs) have emerged as a new-fashioned electrocatalyst in hydrogen evolution reactions (HERs). Oleylamine (OM), a reducing surfactant and solvent, plays a significant role in the assisting synthesis of CZTS NCs due to the ligand effect. Herein, we adopted a facile one-pot colloidal method for achieving the structure evolution of CZTS NCs from 2D nanosheets to 1D nanorods assisted through the continuous addition of OM. During the process, the mechanism of OM-induced morphology evolution was further discussed. When merely adding pure 1-dodecanethiol (DDT) as the solvent, the CZTS nanosheets were obtained. As OM was gradually added to the reaction, the CZTS NCs began to grow along the sides of the nanosheets and gradually shrink at the top, followed by the formation of stable nanorods. In acidic electrolytic conditions, the CZTS NCs with 1.0 OM addition display the optimal HER activity with a low overpotential of 561 mV at 10 mA/cm 2 and a small Tafel slope of 157.6 mV/dec compared with other CZTS samples. The enhancement of HER activity could be attributed to the contribution of the synergistic effect of the diverse crystal facets to the reaction.